PENGARUH PENGEMBANGAN PRODUK PERUMAHAN TERHADAP PENINGKATAN VOLUME PENJUALAN PT INPERSADA PRIMACIPTA PEKANBARU - Asikin, Ref Maulana; Farida, Lena (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
The purpose of this study was to determine the effect of productdevelopment to the increase in sales volume in PT.Inpersada PrimaciptaPekanbaru. In this research, product development as the independent variable (X)and the level of sales volume as the dependent variable (Y). samples used were 51respondents with a sampling technique using Non Probability Sampling withsampling techniques accidental ... ..Overall the data obtained through questionnaires and further processed forstatistical analysis tested as a simple linear analysis, t-test, correlation coefficient,and the coefficient of determination by using SPSS 16 for windows.From the calculation results obtained regression coefficient value of 2,027,where the value of the correlation coefficient indicates a strong enoughrelationship and positive relationship between product development (variable x) tothe level of sales volume (variable y). while the value of the coefficient ofdetermination (R square) of 0.978 means that the overall development of theproduct had a positive influence response to the levels of sales volume amountingto 97.8% hypothesis test results (t) that the value of t is greater than t table ie32.824> 2.00 means that product development and significant positive effect onthe level of sales volume.Keywords: product development, the level of sales volume, PT. InpersadaPrimacipta Pekanbaru